The role of innate immune cells in the tumor microenvironment and research progress in anti-tumor therapy - Lu, Chenglin; Liu, Ying; Ali, Nasra Mohamoud; Zhang, Bin; Cui, Xiaonan (Frontiers in Immunology, 2023)
Innate immune cells in the tumor microenvironment (TME) mainly include macrophages, neutrophils, natural killer cells, dendritic cells and bone marrow derived suppressor cells. They play an anti-tumor or pro-tumor role by secreting various cytokines, chemokines and other factors, and determine the occurrence and development of tumors. Comprehending the role of innate immune cells in tumorigenesis and progression can help improve therapeutic approaches targeting innate immune cells in the TME, increasing the likelihood of favorable prognosis. In this review, we discussed the cell biology of innate immune cells, their role in tumorigenesis and development, and the current status of innate immune cell-based immunotherapy, in order to provide an overview for future research lines and clinical trials.